Forgotten Fibrocytes: A Neglected, Supporting Cell Type of the Cochlea With the Potential to be an Alternative Therapeutic Target in Hearing Loss - Furness, David N. (Frontiers in Cellular Neuroscience, 2019)
Cochlear fibrocytes are a homeostatic supporting cell type embedded in the vascularised extracellular matrix of the spiral ligament, within the lateral wall. Here, they participate in the connective tissue syncytium that enables potassium recirculation into the scala media to take place and ensures development of the endolymphatic potential that helps drive current into hair cells during acoustic stimulation. They have also been implicated in inflammatory responses in the cochlea. Some fibrocytes interact closely with the capillaries of the vasculature in a way which suggests potential involvement, together with the stria vascularis , also in the blood-labyrinth barrier. Several lines of evidence suggest that pathology of the fibrocytes, along with other degenerative changes in this region, contribute to metabolic hearing loss (MHL) during ageing that is becoming recognised as distinct from, and potentially a precursor for, sensorineural hearing loss (SNHL). This pathology may underlie a significant proportion of cases of presbycusis. Some evidence points also to an association between fibrocyte degeneration and Ménière’s disease (MD). Fibrocytes are mesenchymal; this characteristic, and their location, make them amenable to potential cell therapy in the form of cell replacement or genetic modification to arrest the process of degeneration that leads to MHL. This review explores the properties and roles of this neglected cell type and suggests potential therapeutic approaches, such as cell transplantation or genetic engineering of fibrocytes, which could be used to prevent this form of presbycusis or provide a therapeutic avenue for MD.